PENGEMBANGAN BAHAN AJAR BERBASIS PENDIDIKAN MATEMATIKA REALISTIK (PMR) PADA MATERI PROGRAM LINEAR - Mayani, Sri; Rizki, Swaditya (AKSIOMA (Jurnal Pendidikan Matematika), 2016)
The products developed are based teaching materials realistic mathematics education. The purpose of this research is (1) Develop products in the form of teaching materials based on realistic mathematics education they deserve. (2) To determine the effectiveness of teaching materials based on realistic mathematics education on a linear program material. Development steps used is seeking potential and problems, collect data, product design, design validation, design revisions, product testing, product revision, utility testing, product revision, and mass production. The study population was students of class X Vocational High School Muhammadiyah 3 Metro and sample are learners class X1 (experimental group) and learners class X2 (control group). Validation results showed a very decent category with the percentage of 80,72%. The test results showed a small group categorized by the percentage of 69%. The test results showed a large group instructional materials primarily to the percentage of 77% feasible and effective in its use based on the average learning outcomes of students in large groups. Based on this, it can be concluded that (1) developed teaching materials eligible for use in learning. (2) The teaching materials are effective in learning